APPLYING SOCIOLINGUISTICS AND PRAGMATICS IN THE STUDY OF DISCOURSE - Nilufar Xafizovna Ruziyeva; Fotima Ergasheva (Modern American Journals, 2025)
This article explores how sociolinguistics and pragmatics help us understand everyday communication. By looking at how language works in social situations and how people communicate meaning beyond just words, we can better understand human interaction and conversation.
Keywords: Sociolinguistics, pragmatics, discourse analysis, context, speech acts, social meaning, conversation, language variation.